Strategic Growth and Market Position of Artel Electronics Company - Bekzodjon Oblakulov; Sardor Kuvandikov (Academia Open, 2025)
General Background: The consumer electronics industry in Central Asia is experiencing rapid growth, driven by rising demand for affordable and innovative household technologies. Specific Background: In Uzbekistan, Artel Electronics has emerged since 2011 as a dominant local manufacturer, expanding from gas stoves to a portfolio of over 1,500 products across 33 categories. Knowledge Gap: Despite its strong domestic presence, limited international reach, digital engagement, and reliance on local suppliers constrain its global competitiveness. Aims: This study analyzes Artel’s strategic position through internal and external assessments, SWOT, and BCG matrix, to evaluate its marketing mix in B2B and B2C contexts. Results: Findings reveal that Artel’s success stems from its balance of quality and affordability, robust distribution network, and product diversification, while weaknesses include constrained global presence and insufficient e-commerce penetration. Novelty: Unlike prior analyses, this study integrates PESTEL and BCG perspectives to highlight how Artel can leverage sustainable practices, digital platforms, and international market entry to strengthen its positioning. Implications: The research suggests that adopting eco-friendly innovation, expanding digital channels, and targeting niche global segments will enhance Artel’s competitiveness, ensuring sustainable growth in a highly dynamic global electronics market. Highlights: Strong brand recognition and product diversification drive Artel’s market leadership. Limited international presence and weak digital channels remain key challenges. Sustainable innovation and global expansion are crucial for future growth. Keywords: Artel Electronics, Local Business, Business Clients.